2013
DOI: 10.1039/c2cp42856c
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state macroscale voltammetry in a supercritical carbon dioxide medium

Abstract: The electrochemical oxidation and reduction of decamethylferrocene is demonstrated in supercritical carbon dioxide at a macro gold disc electrode at 100 bar and 313 K. Fast mass transport effects were exhibited and the corresponding steady-state voltammetry was observed at high scan rates. A highly lipophilic room temperature ionic liquid that readily dissolved in supercritical CO 2 with acetonitrile as a co-solvent was used as an electrolyte, allowing for a conducting supercritical single phase. Experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Recently Toghill et al 7 suggested, based on their experimental data for the voltammetry of DMFc in scCO 2 /MeCN, that a 60 mm thick liquid layer formed at the working electrode surface and that all of the voltammetry occurred within this layer. This conclusion was based on the results of voltammetry at macrodiscs at scan rates of 25-1000 mV s À1 .…”
Section: Comparison With the Results Of Toghill Et Almentioning
confidence: 98%
“…Recently Toghill et al 7 suggested, based on their experimental data for the voltammetry of DMFc in scCO 2 /MeCN, that a 60 mm thick liquid layer formed at the working electrode surface and that all of the voltammetry occurred within this layer. This conclusion was based on the results of voltammetry at macrodiscs at scan rates of 25-1000 mV s À1 .…”
Section: Comparison With the Results Of Toghill Et Almentioning
confidence: 98%
“…This was particularly noted in a recent publication by Toghill et al [21] in which macroscale voltammetry of decamethylferrocene (DMFc) was undertaken in a scCO 2 /acetonitrile medium. At moderately fast scan rates the DMFc voltammetric signal transitioned from macroscale peak shape to a steady state profile (Fig.…”
Section: Supercritical Carbon Dioxide (Scco 2 )mentioning
confidence: 95%
“…An alternative strategy proposed to enhance the ionic conductivity of the scCO 2 is to add a highly polar and miscible co-solvent. To-date methanol [18,19], dimethylformamide [20] or acetonitrile [18,21] has been employed. Organic co-solvents form a single phase with scCO 2 and considerably improve the solubility of ionic species.…”
Section: Supercritical Carbon Dioxide (Scco 2 )mentioning
confidence: 99%
“…Addition of acetonitrile (CH 3 CN) as a polar co-solvent increases the effective dielectric constant for the fluid and hence the solubility of electrolytes and the solution conductivity [20]. Supercritical CO 2 /CH 3 CN has been used in our group for the electrodeposition of both copper [14] and silver [15] and Toghill et al [21] synthesised and purified as described elsewhere [13,20]. Carbon dioxide (99.999 % SCF grade, BOC) was used without further purification.…”
Section: Introductionmentioning
confidence: 99%